Mechanisms for Professional Training of Future Preschool Educators in Higher Educational Institutions - Guzal Malikovna Nazirova (International Journal of Formal Education, 2025)
The article examines the training of future preschool educators as a pedagogical problem, examines and highlights the current state of professional training of educators, the mechanisms of organization and management of professional training processes in higher education institutions, professional and personal development of educators.